2016
DOI: 10.1118/1.4960003
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Development of a 3D printed subresolution sandwich phantom for validation of brain SPECT analysis

Abstract: The authors have demonstrated the ability to create physically realistic HMPAO SPECT simulations using a novel head-shaped 3D printed subresolution sandwich method phantom. The phantom can be used to validate all neurological SPECT imaging applications. A simple modification of the phantom design to use thinner slabs would make it suitable for use in PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 65 publications
0
22
0
3
Order By: Relevance
“…, aiming to be filled with a solution, such as radiotracer or “bone” material K 2 HPO 4 . A completely different approach was used by Negus et al who operated an FDM 3D printer to build transaxial slabs, and operated a standard Hewlett‐Packard Officejet Pro 8100 printer to print radioactive paper sheets . To do that, the radioisotope was inserted in the ink cartridge of the printer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, aiming to be filled with a solution, such as radiotracer or “bone” material K 2 HPO 4 . A completely different approach was used by Negus et al who operated an FDM 3D printer to build transaxial slabs, and operated a standard Hewlett‐Packard Officejet Pro 8100 printer to print radioactive paper sheets . To do that, the radioisotope was inserted in the ink cartridge of the printer.…”
Section: Resultsmentioning
confidence: 99%
“…Sub‐resolution sandwich phantom with radioactive paper sheets between each slab . Figure license: Negus, et al #bib2016, Technical Note: Development of a 3D printed subresolution sandwich phantom for validation of brain SPECT analysis (Copyright by John Wiley and sons).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies for different imaging systems have reported on phantoms that recapitulate the heterogeneous anatomical regions of human physiology. [18][19][20][21][22][23] Nonetheless, most of the existing phantoms for SPECT, PET, CT, and MRI are not suitable for multimodality imaging. They are limited in their abilities to repeat and reproduce the heterogeneous nature of the tumor.…”
Section: Introductionmentioning
confidence: 99%